Upaya Peningkatan Produktivitas Tanaman Pangan Melalui Pendidikan Diagnosa Visual Hara Tanaman - Riduansyah, Riduansyah; Suswati, Denah; Nuriman, Muhammad; Romiyanto, Romiyanto (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Increasing farmers' human resources in evaluating plant nutrients is an important part of increasing plant productivity, family food security and farmer income. Therefore, we researchers, carry out training activities for farming communities. The training was held in the Pal Sembilan village office hall, Sungai Kakap District. Attended by village officials, heads of farmer groups and members of farmer groups, Pal Sembilan village with a total of 30 people. The training was carried out by discussing procedures for visually observing deficiencies and excesses of plant nutrients. Farmers gain knowledge through short lectures, brochures with visual images of plant nutrients, and land management recommendations. Recommendations for improvement on land that has a pH of 4.5 and land conditions that are characterized by oxidized Fe, Al, and Mn are to wash the land first, or rinse the land first from Fe, Al, and Mn poisoning, and the recommended application of dolomite is 2 tons. /ha for land that does not have water management, during the process of increasing soil pH, it is not recommended to use N fertilizer, and spraying fungicides to reduce fungi that previously lived in acidic soil conditions. The extension location has symptoms of potassium deficiency, so it is recommended to provide rice straw to reduce the need for inorganic potassium fertilizer by 70-90%.